Determining members’ trust in cooperative: application of value cocreation behavioural scale / Yusman Yacob … [et al.] - Yacob, Yusman Yacob; Ali, Jati Kasuma; Lajuni, Nelson; Pakasa, Umi Insyirah; Punding, Azlan Yusof; Shamsuddin, Noor Emma (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Recently there are several numbers of research on value co-creation behaviour that continuously grow in the service marketing literatures. Customer is always a co-creator of value and they play an important role as an active player in value co-creation. In a cooperative context, member of a cooperative plays an important role to ensure the co-creation of value can be strategized. On the other hand, it will help both cooperative and member as in a cooperative setting, the cooperative’s business as a service provider is owned by their respective members. Therefore, it requires active participation among members in the service delivery and also more extra roles in economic and social activity in cooperatives. The aim of this study is to examine the relationship between value co-creation behaviour and their trust. Measurement of value cocreation behaviour are consisting of four (4) dimensions, namely information seeking, information sharing, responsible behaviour and personal interaction. The minimum sample size was determined through G-Power analysis. By appropriating the quantitative approach, 395 copies were collected and deemed usable after data cleaning procedure. Partial least squares structural equation modelling was employed to test the hypotheses empirically. Results from this study can be utilized by related Ministry and cooperative sector to determine their members’ trust by utilizing the cooperative value co-creation behaviour scale which has been established from this study. This study contributes to the knowledge and practice in the cooperative industry by underscoring the importance of value co-creation behaviour in determining members’ trust and policy making agenda.